Gated Blood Pool SPECT and Phase Analysis to Assess Simulated Wolff-Parkinson-White Syndrome in the Baboon - Dormehl, Irene C.; van Gelder, A. L.; Hugo, N.; Weller, R.; Stanton, J. J.; Beverley, G. H.; Clausen, M. (Nuklearmedizin - NuclearMedicine, 1993)
This study assesses the diagnostic potential of a tomographic technique with phase analysis to detect premature electroventricular contraction patterns simulated by pacing in the baboon. The data of gated SPECT were analysed by backprojection of the Fourier coefficients, followed by angulation and integration to thick slices of the entire ventricular mass yielding separate ventricular contraction patterns in three perpendicular views. Electrodes were implanted in each baboon: at the sinu-atrial node; posterior, left ventricular; anterior left ventricular; on the left and the right lateral ventricular walls. The atrium was stimulated throughout at a fixed rate. Subsequent ventricular stimuli followed during the QRS complex, such to invoke the appearance of pre-excitation QRS morphology. The first points of activation (FPA) from this algorithm were correctly detected for the RV, for the anterior and posterior sites, although the latter two manifested first points in the RV. LV pacing manifested also as a FPA in the RV, but was followed by a true subsequent point in the LV.Diese Studie untersucht die diagnostischen Möglichkeiten einer tomographischen Aufnahmetechnik mit Phasenanalyse. Die Methode dient der Erkennung einer vorzeitigen elektroventrikulären Erregung durch Elektrostimulation der Ventrikel in einem Affenmodell. Die Fourier-Koeffizienten der getriggerten SPECT-erfaßten Daten wurden dazu rückprojiziert, doppelanguliert und zu dicken, ventrikelumfassenden Schichten zusammengefaßt. So ergaben sich Kontraktionsmuster, getrennt für jeden Ventrikel, in drei senkrechten Ansichten. Jedem Affen wurden fünf Elektroden implantiert: am Sinusknoten; posterior und anterior am linken Ventrikel; links lateral am linken Ventrikel und an der rechten Seitenwand. Während des Experiments wurde der Vorhof mit fixer Frequenz stimuliert. Die ventrikuläre Stimulation erfolgte während des QRS-Komplexes nach einer atrioventrikulären Verzögerung, deren Dauer eine vorzeitige Erregung im QRS-Komplex erkennen ließ. Aktivierungspunkte der Erregung, die durch die neue Methode bestimmt wurden, waren korrekt für den RV, auch für die anteriore und posteriore Erregung, jedoch rechts ventrikulär bei beiden letzten Versuchen. Stimulation im LV wurde als Aktivierungsort im RV erkannt, aber gefolgt von einem korrekt erkannten Aktivierungspunkt im LV.
Keywords: Stimulated WPN syndrome; phase analysis; baboons